An Investigation of the Monotonic and Cyclic Behavior of Additively Manufactured TPU - Sara Ricci; Alberto Pagano; Andrea Ceccacci; Gianluca Iannitti; Nicola Bonora (Engineering Proceedings)
The mechanical properties of rubber-like materials, such as their high flexibility and durability, make them widely applicable across different industrial fields, from aerospace to healthcare and, most notably, the automotive sector. In operative conditions, these materials experience large deformations and repeated loadings, which may result in inelastic and dissipative phenomena. The aim of this study is to investigate the mechanical properties of two thermoplastic elastomeric materials manufactured with the Fused Filament Fabrication (FFF) technique: unfilled thermoplastic polyurethane (TPU) and TPU reinforced with carbon nanotubes (CNTs). Several experimental tests were performed to assess the response of both materials under monotonic and cyclic loadings. The addition of CNTs led to improved stiffness and strength without compromising elasticity. Under repeated loadings, both materials were characterized by the Mullins and viscous effects. However, the presence of CNTs was found to slightly amplify these inelastic phenomena. The integration of additive manufacturing technologies, combined with the use of innovative fillers, can offer design and performance optimization to all those components that strongly rely on elastomers.